Pemodelan pemilihan kenderaan bagi perjalanan antara Bangi dengan Kuala Lumpur - Riza Atiq O.K.Rahmat,; Lim , Wai Yip (2000)
Modelling the modal choice of transport is an important step in urban transport planning. In this study, modelling the transport modal choice of Bandar Barn Bangi residence going to work in Kuala Lumpur was conducted. The trip makers have three choices of transport mode, that is call commuter train and bus. Motocycles and taxis are ignored due to their in extensive usage for this kind of trip. It was found that monthly income, travel cost (including parking charges) and travel times are the main factors that influence the transport choice. The relationships of these variables to the transport choice were formulated in the form of trip end model and trip interchange models. In the trip end model, two stages decision structure with logistic function was adopted. Monthly income was found to give a good probability ode. In the trip interchange model, a single stage decision structure with multinomial logic function was adopted. The developed model was found out to closely replicate the actual transport mode choice when independent variables such as monthly income, travel cost by cal travel time for both modes of transport and the ratio of fare charges monthly income of commuter train and bus were included in the model